Pemanfaatan Mulsa Organik Pueraria javanica dan Kompos Pelepah Kelapa Sawit Terhadap Penghambatan Perkecambahan dan Pertumbuhan Anakan Gulma Borreria alata (Aublet) DC (Jurnal Agro Teknologi Tropika, 2013)
The objectives of this research is to evaluate the effect of two organic mulches of Pueraria javanica and the palm oilstem compost with different thickness on seed germination and growth of Borreria alata. The observed data wereanalyzed using Analysis of Variance (ANOVA) and the significant differences among the treatment means were determinedusing Duncanâs Multiple Range test with test level 5%. The results showed that all organic mulches decreased B. alatagermination and growth germination and growth. Mulch of Pueraria javanica with thickness of 2.5 cm reduced weedgermination as much as 76.29% and growth 44.26%. Palm oil stem compost with thickness of 2.5 cm gave the significanteffect on the decrease of weed germination i.e 86.60% and growth i.e 32.79%. The 7.5 cm and 12.5 cm thickness mulchingwith P. javanica and palm oil stem compost gave no germination of weeds.Keywords: Borreria alata, organic mulch, Pueraria javanica, palm oil stem compost